Pengelolaan Program Kesehatan Masyarakat Melalui Forum Kesehatan Kelurahan Siaga di Kelurahan Plalangan - Anggraeni, Dewi; Kisworo, Bagus (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
The aims of this research describing the management of the program health Forum of the village standby (FKKS), supporting factors and impeding in realizing the public health in Kelurahan Plalangan. The study used a qualitative, discrete approach. Data collection techniques are conducted with interviews, observations, and documentation. The validity technique uses the triangulation of the source, method, and theory. Data analysis techniques in research using data collection, data reduction, data presentation, and withdrawal of conclusions. The results of the research obtained that the process of management of FKKS in the program of Plalangan has been running well based on the theory of programming and systematic program starting from the activities of planning, organizing, The process of implementing, monitoring, and ending with the evaluation process. Supporting factors for the management of this program is public awareness of the importance of health, facilities and infrastructure, coaching, and funding is adequate. While the inhibitory factor is still the least cadres who mastered IT, not all citizens who participated in the program due to busy activities.